Wayward Christian Soldiers: Freeing the Gospel from Political Captivity - Chapman, G. Clarke (A journal of church and state, 2009)
This book arose from an op-ed (of the same title) written by Charles Marsh for the New York Times, in January 2006. Clearly it struck a public nerve, for it was widely emailed and the author received more than five-hundred letters in response. Apparently many American readers, both churched and unchurched, have been greatly disturbed by the ascendency of right-wing forms of evangelicalism into the public spotlight, yet have not adequately articulated their unease. Marsh, one of Protestantism's most talented young theologians, now has expanded his theme and provides such readers with documentation and a wider historical context.